The Significance of Pilgrimage Tourism at a New Stage of Development of Uzbekistan - Adilov, Z.H.; Muxammadjonov, A. U.; Po’latov, X. I. (European Journal of Life Safety and Stability (2660-9630), 2022)
In Uzbekistan, since 2016, tourism has been declared one of the most important sectors of the country's economy. During these years, along with all areas of tourism, extensive work has been done to develop pilgrimage tourism. As a result, the number of tourists visiting our country has increased significantly. This article is devoted to the development of pilgrimage tourism and its results in building the "third renaissance" in Uzbekistan.